2009
DOI: 10.1021/jp806190w
|View full text |Cite
|
Sign up to set email alerts
|

Manipulation of PtAg Nanostructures for Advanced Electrocatalyst

Abstract: Attempts are made in this study to manipulate nanostructures of Pt-flecks on Ag nanoparticles (Pt m ∧ Ag) for advanced electrocatalysts by reflux citrate reduction of Pt from Pt II Cl 4 2or Pt IV Cl 6 2ions in solution containing Ag colloids at different atomic Pt/Ag ratio (m). Characterizations with UV-vis, SERS, XPS, and XRD showed a gradual Pt covering of the Ag colloids with increasing m when Pt II Cl 4 2was the precursor of Pt (Pt m ∧ Ag-A samples). However, due to an involvement of the galvanic replaceme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
60
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(63 citation statements)
references
References 55 publications
3
60
0
Order By: Relevance
“…The phase diagram predict the difficulty to form an Ag/Pt alloy when the Pt component is higher than 5 % of the molar ratio, due to the large miscibility gap at temperatures below 900 8C. [51,52] However, Zhao et al [52] have recently reported that "fully alloyed" Pt 50 Ag 50 nanoparticles could be prepared by co-reduction of Ag + and PtCl 6 2À by NaBH 4 at room temperature, which is in agreement with our results. Herein, the formation of a Pt/Ag alloy structure is kinetically favored, driven by the successive leaching of Ag atoms (a pushing out force) and corresponding deposition of Pt atoms (a landing force).…”
Section: Characterization Of Nanotubular Mesoporous Alloyssupporting
confidence: 90%
“…The phase diagram predict the difficulty to form an Ag/Pt alloy when the Pt component is higher than 5 % of the molar ratio, due to the large miscibility gap at temperatures below 900 8C. [51,52] However, Zhao et al [52] have recently reported that "fully alloyed" Pt 50 Ag 50 nanoparticles could be prepared by co-reduction of Ag + and PtCl 6 2À by NaBH 4 at room temperature, which is in agreement with our results. Herein, the formation of a Pt/Ag alloy structure is kinetically favored, driven by the successive leaching of Ag atoms (a pushing out force) and corresponding deposition of Pt atoms (a landing force).…”
Section: Characterization Of Nanotubular Mesoporous Alloyssupporting
confidence: 90%
“…[35][36][37] Coincident with the results of other studies, 35,37 we only found a marginal composition-depending shift of the Pt 4f peak. Therefore, only the Ag 3d detail spectra of all synthesized NTs are shown in Fig.…”
Section: Double-walled Ag-pt Nts Fabricated By Galvanic Replacement Asupporting
confidence: 87%
“…6 Conventional replacement reactions are mostly confined to aqueous solutions, where various aspects including speciation, reaction mechanism, kinetic control and resultant structure tuning have been extensively investigated. [7][8][9][10] Ionic liquids (ILs) have recently become attractive media for fabrication of metallic nanostructures by the galvanic replacement strategy. [11][12][13] ILs are generally aprotic with relatively high viscosity and provide a different chemical environment compared to molecule solutions.…”
Section: Introductionmentioning
confidence: 99%